Examining the Impact of FinTech on Banks’ Consumer Lending, Credit Risk, and Financial Performance: The case of the United States and China - Madjleis Taklimi, Zahra (2024)
In light of the inherent limitations of traditional banks’ consumer lending models and the distinctive advantages observed in FinTech and BigTech lenders, coupled with their remarkable growth trajectories, it comes as no surprise that industry experts and researchers widely regard the FinTech phenomenon as a disruptive innovation for the banking sector. While the prevailing sentiment in the literature tends to cast FinTech as a formidable threat to traditional banks, it is essential to recognize that, if harnessed effectively, FinTech, as a cutting-edge technology, holds the potential to enhance banks’ consumer lending capabilities, elevate financial performance, and diminish credit risk.